ANALISIS KANDUNGAN LOGAM HG (MERCURY) PADA AIR SUNGAI MENGGUNAKAN METODE SPEKTROFOTOMETRI SERAPAN ATOM (SSA) - Muhammad Rifky Ulliyah (DE FACTO : Journal Of International Multidisciplinary Science, 2024)
The purpose of this study was to determine the Circulation Service System at Bina Darma University Library Palembang. This research discusses the activities of the circulation service system in the library, and explains the challenges faced in circulation services in the library which is very important because it is one of the activities directly related to users or users. The research method is descriptive qualitative with data collection techniques through observation and literature study. The result of the research is that loyalty activities are also a means of measuring the success of the library organization. Circulation Service activities in the library are always directed and focused on how to provide good service and information according to the wishes of users or users. The various loyalty activities carried out by the library are all aimed at utilizing library materials and facilities owned by the library.